The manuscript of the scholar Mullah Abd al-Rahman al-Binjwini on the (Jama' Al-jawame') From the topic of (All) from the topics of (Al-letters) to (General): Study and investigation (Raparin Journal of Humanities (RJH), 2023)
This study attempts to investigate part of a valuable manuscript on the book (Jama' Al-jawame') in the Science of Fundamentals of Jurisprudence (Elm Usul al-Fiqih) by the scholar Mulla Abdul Rahman Al-Binjwini (died in:1319m)، From the topic of (Al-kul) from the topics of (Al-Huruf) to (al-Aam)، Relying on three copies of the manuscript with the author's life، study of the book، the author's approach to the manuscript، a description of the written versions، my work in the investigation، and at the end the list of sources and references.